Influence of Substitution of Maize with Wheat Bran and Rice Bran in the Rations on Growth Performance and Nutrient Utilization in Local Pig (Zovawk) of Mizoram - Yendrembam, Mery Chanu; Samanta, Arup Kumar (Indian Journal of Animal Nutrition, 2018)
Twenty growing indigenous pigs (6-7 months of age) of Mizoram (Zovawk) of average body weights (22.07Â±1.15 kg) were randomly distributed into 4 groups of 5 animals each to study the effect of feeding wheat bran and rice bran based diet by replacing maize on growth performance and nutrient utilization. The animals in group G1 (control) were fed standard pig grower concentrate mixture (BIS, 1986) while in groups G2, G3 and G4, maize was replaced by wheat bran and deoiled rice bran (in equal proportion) at 60, 80 and 100% levels, respectively. During the feeding trial of 90 days, the average DM intake (g/head/day) was significantly higher (P<0.05) in group G4. Average daily weight gain (kg/day) was 0.23, 0.21, 0.16 and 0.15 for G1, G2, G3 and G4 respectively with corresponding value of feed conversion ratio for G1, G2, G3 and G4 was 6.19, 6.53, 8.77 and 10.04. The ADG and FCR was better in group in groups G1 and G2 compared to groups G3 and G4. The digestibility of DM, CF, EE and NFE was lower (P<0.05) in G3 and G4 as compared to G1 and G2. Hence, maize could be replaced up to 60% by wheat bran and deoiled rice bran in equal proportions safely without any undesirable effects on growth and nutrient utilization in the diet of local pigs (Zovawk) of Mizoram.